2013
DOI: 10.1002/asia.201201025
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Helical Mesoporous Tantalum Oxide Nanotubes through a Sol–Gel Transcription Approach

Abstract: The TaO of nanotubes: Single‐handed helical Ta2O5 nanotubes with mesopores in the walls were prepared using the self‐assemblies of the low‐molecular‐weight gelators as the templates. The handedness of the Ta2O5 nanotubes was controlled by organic self‐assemblies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
46
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(48 citation statements)
references
References 59 publications
2
46
0
Order By: Relevance
“…(Figure 1). [13] Preparation of Single-Handed, Helical, 4,4'-Biphenylene-Bridged Polybissilsesquioxane Nanotubes LMWG l,l-(or d,d-)8Val11PyClO 4 (35 mg, 0.034 mmol) and BTSB (0.46 mmol) were dissolved in absolute ethanol (1.0 mL) under reflux in a test tube. After cooling to room temperature, an opaque gel was formed.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…(Figure 1). [13] Preparation of Single-Handed, Helical, 4,4'-Biphenylene-Bridged Polybissilsesquioxane Nanotubes LMWG l,l-(or d,d-)8Val11PyClO 4 (35 mg, 0.034 mmol) and BTSB (0.46 mmol) were dissolved in absolute ethanol (1.0 mL) under reflux in a test tube. After cooling to room temperature, an opaque gel was formed.…”
Section: Resultsmentioning
confidence: 99%
“…If reactions were carried out in alcohol with atmospheric moisture as the reactant, singlehanded, helical nanotubes were obtained. [13] The chirality at the ngstrom level has also been observed by means of CD spectroscopy. Herein, single-handed, helical, 4,4'-biphenylene-bridged polybissilsesquioxane nanotubes were prepared through a diffusion approach.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…The LMWGs for the preparation of Ta 2 O 5 nanotubes were shown in Fig. 27 Herein, although the LMWG concentration in the reaction mixtures was increased, single-handed helical Ta 2 O 5 nanotubes were also obtained. It has been reported that LL-and DD-8Val11PyClO 4 in ethanol at a concentration of 10 mg mL À1 can self-assemble into le-and right-handed twisted nanoribbons, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…4 Silicon microtubes have been prepared via the evaporation of sodium from NaSi disks. [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] The optical chirality of these materials has been studied using circular dichroism (CD), and diffuse reectance circular dichroism (DRCD). 6 Although materials with helical morphologies can be obtained, it is difficult to obtain single-handed materials using these approaches.…”
Section: Introductionmentioning
confidence: 99%